2010
DOI: 10.1007/bf03326196
|View full text |Cite
|
Sign up to set email alerts
|

Distribution behavior of polycyclic aromatic hydrocarbons in roadside soil at traffic intercepts within developing cities

Abstract: A study of polycyclic aromatic hydrocarbons pollution in roadside soil was conducted in developing city environment of northern India during autumn and winter season to ascertain the contamination levels and their distribution behavior in soil. The concentration of polycyclic aromatic hydrocarbons was determined at ten locations of Jalandhar city, Punjab in India at 1, 2 and 3 m distances from roadside in soil covering all the major traffic intercepts within city. The samples were extracted in acetone and dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The levels of present study were much lower than the reported levels out of road dust of industrial city, Korea (11,840-245,120 ng g −1 ) (Lee & Dong, 2011). The levels were higher than the reported levels from Shanghai, China (6875-32,573 ng g −1 ) (Liu et al, 2007), Delhi, India (1062-9652 ng g −1 ) (Agarwal, 2009), Dalian, China (1890-17,070 ng g −1 ) (Wang, Yang, Jia, Zhou, & Li, 2009), Tehran, Iran (11,107-24,342 ng g −1 ) (Samimi et al, 2009), Hunan, China (3515-24,488 ng g −1 ) (Long, Chi, Qing, Dai, & Wu, 2011) and Punjab, India (770-46,460 ng g −1 ) (Kumar & Kothiyal, 2011). The comparison of street dust PAHs concentrations estimated in the present study with previous works depicts higher levels of PAHs in the present study.…”
Section: Seasonal and Spatial Variation Of Pahsmentioning
confidence: 97%
“…The levels of present study were much lower than the reported levels out of road dust of industrial city, Korea (11,840-245,120 ng g −1 ) (Lee & Dong, 2011). The levels were higher than the reported levels from Shanghai, China (6875-32,573 ng g −1 ) (Liu et al, 2007), Delhi, India (1062-9652 ng g −1 ) (Agarwal, 2009), Dalian, China (1890-17,070 ng g −1 ) (Wang, Yang, Jia, Zhou, & Li, 2009), Tehran, Iran (11,107-24,342 ng g −1 ) (Samimi et al, 2009), Hunan, China (3515-24,488 ng g −1 ) (Long, Chi, Qing, Dai, & Wu, 2011) and Punjab, India (770-46,460 ng g −1 ) (Kumar & Kothiyal, 2011). The comparison of street dust PAHs concentrations estimated in the present study with previous works depicts higher levels of PAHs in the present study.…”
Section: Seasonal and Spatial Variation Of Pahsmentioning
confidence: 97%
“…The prepared samples were kept preserved in an ambercolored sample tubes in refrigerator below 4°C for analysis. The samples were later analyzed for the types and concentration of PAHs by GC (Kumar and Kothiyal 2011).…”
Section: Extraction Of Pahsmentioning
confidence: 99%
“…The impact of automobile emission on environment, predominantly on soil, air and water is increased day by day. Automobile emissions have shown a tremendous impact on the environment during the last few years (Kumar and Kothiyal, 2011). Proliferation of motor transport, rather than industrial activities, is advanced in political and/or commercial cities as providing the main contribution to growing levels of pollution such as PAHs.…”
Section: Introductionmentioning
confidence: 99%